PERKEMBANGAN AKUNTANSI KEPERILAKUAN DAN DAMPAKNYA PADA PENELITIAN AKUNTANSI DI INDONESIA - Khomsiyah , (Media Riset Akuntansi, Auditing & Informasi, 2001)
This paper discusses about the development of behavioral accounting and how it influenced the research in behavioral accounting. Several interest fields in behavioral accounting research are discussed to provide an overview of current behavioral accounting research opportunities. The research methodology and several difficulties inherent in those researches presented in this paper. The behavioral accounting research in Indonesia will discussed in the last of this paper.